Los proyectos de electrificación solar fotovoltaica a través de las ONG - IPADE (Revista Española de Desarrollo y Cooperación, 2023)
There is a great inequality in the use of the energy between the North and the South, the rich and the poor, men and women. Since the access to modern services of energy is an indispensable requirement for the increase of productivity and the improvement of life there’s a challenge to be faced: the means and wills to produce and to use energy that is economic, social and environmentally sustainable, turning therefore the energy into an important instrument for sustainable development. Since 1987 Fundación IPADE develops projects of solar electrification in different countries from Africa, Latin America and Asia, trying to promote a kind of growth compatible with sustainability of natural resources, that is, incorporating renewable sources of energy.